A Study On Hpo From The Employees’ Perspective In Selected Public Sector In Pakistan - Kalimullah, Kalimullah (2019)
This study aims to test the five indicators of High Performance Organization (HPO) framework derived by the Professor De Wall in the selected public sector organization in Pakistan with the purpose to identify the performance status and to propose the solution to improve the identified poor factors resulted from the tested HPO framework. For this purpose, explanatory sequential method of mix methodology is applied whereby the quantitative method is used to assess the performance status and the qualitative method is used to propose the improvement solutions to the public sectors organizations. HPO framework had a structured questionnaire of 35 items and it was used to collect data from 513 respondents from three selected public service organizations of Pakistan. The quantitative study results indicated low performance status of public sector organizations. This study found that HPO framework explained 27.5% variance in the performance of public sector organizations in Pakistan. Therefore, this study concluded that the HPO framework is applicable in Pakistani context but it is not a “quick fix” to achieve HPO in Pakistan. In the qualitative method, there were twelve interviews attending to three main interview questions had been conducted in the same organization to the top management of public sector organizations in Pakistan. Thematic network analysis was applied to analyze these public organizations’ understanding on HPO, and to explore the reasons of low mean score of the tested factors in the HPO framework. This study concluded that there is good level of understanding on HPO in public sector organizations of Pakistan, however, the practiced of HPO was found missing in the public sector organizations.